2017
DOI: 10.18632/oncotarget.22619
|View full text |Cite
|
Sign up to set email alerts
|

Investigation ofTCF7L2, LEPandLEPRpolymorphisms with esophageal squamous cell carcinomas

Abstract: Single nucleotide polymorphisms (SNPs) in energy metabolism related gene may be key agents in the development of human malignancies. In this study, we aimed to examine the association of transcription factor 7-like 2, Leptin (LEP) and LEP receptor (LEPR) polymorphisms with esophageal squamous cell carcinoma (ESCC). A total of 507 ESCC cases and 1,496 controls were enrolled. We found that LEPR rs6588147 AA genotype was associated with ESCC risk (AA vs. GG/GA: adjusted OR=1.90, 95%CI=1.00–3.61, P=0.049). In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…Nine were population-based,27,28,30,33,37,38,43,44,50 and 22 case–control were hospital-based studies 21,26,29,31,32,3436,39–42,4549,51–54. Of all the eligible studies, 11 focused on breast cancer,33,3740,44,48,49,51,53 four focused on colorectal cancer (CRC),31,32,41,52 three focused on prostate cancer (PC),26,30,34 and 13 focused on other cancers 21,27–29,35,36,42,43,4547,50,54. Other information includingd case–control studies in the pooled analysis is summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Nine were population-based,27,28,30,33,37,38,43,44,50 and 22 case–control were hospital-based studies 21,26,29,31,32,3436,39–42,4549,51–54. Of all the eligible studies, 11 focused on breast cancer,33,3740,44,48,49,51,53 four focused on colorectal cancer (CRC),31,32,41,52 three focused on prostate cancer (PC),26,30,34 and 13 focused on other cancers 21,27–29,35,36,42,43,4547,50,54. Other information includingd case–control studies in the pooled analysis is summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The genotypes of BTLA rs16859629, rs1982809, rs2171513 and rs3112270 SNPs were analyzed using a SNPscan Kit (Genesky Biotechnologies Inc., Shanghai, China) as described previously [22][23][24]. PCR process was conducted in a 20-μl mixture volume in 96-well plates.…”
Section: Genotypingmentioning
confidence: 99%
“… 35 As for esophageal cancer, an Australian study showed LEP G19A polymorphism was inactive for esophageal carcinogenesis, 36 which was in line with the findings of a Chinese study. 37 However, another Chinese study indicated that LEP G19A polymorphism contributed to less risk for esophagogastric junction adenocarcinoma. 38 As for prostate cancer, two studies obtained it was not heavily associated with LEP G19A polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…This polymorphism was correlated to cancer risk. [33][34][35][36][37][38][39][40][41][42][43][44][45] However, the existing findings in different types of cancers are discrepant. Furthermore, no researchers have studied the relationship between G19A polymorphism and the risk of GC.…”
Section: Introductionmentioning
confidence: 99%